La tecnologia blockchain nella strategia aziendale. Inquadramento contabile e profili di valutazione economica - (:unkn) unknown (Università della Calabria, 2023)
Distributed Ledger Technology (“DLT” for short) has led to the proliferation of Blockchain technology, which makes it possible to use specific cryptographic algorithms that guarantee the authenticity, integrity and origin of data through the creation of computer codes that uniquely intercept information flows, impacting multiple sectors of economy - with particular attention to the supply chain and the financial sector. The particular aspect of this technology, which now enables a new digital paradigm, is based on the logic of decentralization of information flows, consensus and immutability, with the aim of creating scenarios of collaboration based on transparency, minimization of fixed costs and trust.
Dottorato di Ricerca in Scienze Economiche e Aziendali. Ciclo XXXV
Keywords: Blockchain; Strategia aziendale; Supply Chain; Bilancio; Valutazione economica